THE INTERNET AS A HEALTH INFORMATION IN DECISION MAKING OF PREGNANT WOMEN - Nyoman Anita Damayanti; Ratna Dwi Wulandari; Ilham Akhsanu Ridlo; Nadhif Alfia Charista Kusniar; Asrining Pangastuti (Indonesian Journal of Health Administration, 2022)
Background: Maternal and Child Health (MCH) is still becoming a health problem in Indonesia. One of the causes of maternal mortality is the speed of decision making in the family. Decision making is influenced by knowledge, awareness, family shape and culture in the neighborhood. Aims: the study aimed to identify and analyze the relationship between the use of the internet as a health information and maternal decision-making regarding emergency help Methods: This study used a mixed-method approach. The sample of 175 respondents. Data analysis performed in this study was frequency analysis, cross tabulation and chi-square. Results: There were 40% of respondents used the internet as a source of pregnancy information. Pregnant women had the information about pregnancy from google, instagram and whatsApp group. There were 45.70% of them have made decisions independently regarding the emergency relief. Chi-square analysis showed a p-value = “0,000” with a contingency coefficient of 0,368 indicating the use of the internet as a health information related to decision making of pregnant women regarding emergency relief. Conclusion: The conclusion of this study is that there were pregnant women who were using the internet for health information and the majority of pregnant women had made decisions regarding emergency relief independently.